TIPOGRAFI DALAM KUMPULAN SAJAK MANTRA CINTA KARYA ABDUL KADIR IBRAHIM - deci lestari; M.Nur Mustafa; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Abstract: This research is entitled Typography in Abdul Kadir Ibrahim's Collection of Love Mantra Verses. The background of this research is that typography is present as a freedom from the expression of the writer to give birth to his poems. The poet's freedom is felt when a work has essential freedom, one of which is not bound by rules, forms, and lines. The creative process in giving birth to a poem is inseparable from the imagination of the poet's exploration. The purpose of this study is to describe the typography of a collection of love poems written by Abdul Kadir Ibrahim and describe the intrinsic elements in the collection of poems of love mantra by Abdul Kadir Ibrahim, which are related to the meaning seen through Saussure's semiotic approach. This research is descriptive qualitative research that describes and describes the results of the research conducted. Based on research, the author found that typography made by poets mostly relates to what the poet wants to convey to the reader.Key Words: Typography, collection of poems, love spells, Abdul Kadir Ibrahim.